Pengaruh Upah, Modal Usaha, dan Nilai Produksi Terhadap Penawaran Tenaga Kerja Pada UMKM Sektor Riil - Andayani, Widya; Murjana Yasa, I.G.W (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 4, April 2013 (pp. 173-225), 2013)
Developing micro, small , and medium enterprises is one of the government’s efforts in realizing national development. It can provides employment in large numbers. This research to analyze the effect of wages, capital, and production values  to labor supply in micro, small, and medium enterprises of the real sector in West Denpasar district, Denpasar. Data collected from the research location that used Proportionate Stratified Random Sampling method and multiple linier regretion as the analysis method. To analyze simultan and partial effect this research used F test and t test. The result has shown that the wages variable, the capital, and the production values simultaneously affect the labor supply in the real sector of micro, small, and medium enterprises. Whereas, partially, wages, capital, and production has significant and positive impact on the labor supply of the real sector of micro, small, and medium enterprises  in West Denpasar District, Denpasar.
Keywords: Labor , UMKM , West Denpasar